The Beta-Diversity of Siganus fuscescens-Associated Microbial Communities From Different Habitats Increases With Body Weight - Wu, Yongjie; Xiao, Fanshu; Wang, Cheng; Shu, Longfei; Zheng, Xiafei; Xu, Kui; Yu, Xiaoli; Zhang, Keke; Luo, Hongtian; Yang, Yufeng; He, Zhili; Yan, Qingyun (Frontiers in Microbiology, 2020)
Fish-associated microbial communities play important roles in host growth, health and disease in the symbiont ecosystem; however, their diversity patterns and underlying mechanisms in different body habitats remain poorly understood. Siganus fuscescen is one of the most important consumers of macroalgae and an excellent natural marine source of nutritional lipids for humans, and widely distributes in shallow coastal areas. Here we systematically studied the microbial communities of 108 wild S. fuscescens in four body habitats (i.e., skin, gill, stomach and hindgut) and surrounding water. We found that the β-diversity but not α-diversity of fish-associated microbial communities from each habitat significantly (p < 0.05) increased as body weight increased. Also, opportunistic pathogens and probiotics (e.g., Pseudomongs, Methylobacterium) appeared to be widely distributed in different body habitats, and many digestive bacteria (e.g. Clostridium) and several key carbohydrate metabolic pathways were abundant in the hindgut. Additionally, the abundances of some core OTUs associated with digestive bacteria, ‘Anaerovorax’ (OTU_6 and OTU_46724) and ‘Holdemania’ (OTU_33295) in the hindgut increased as body weight increased. The quantification of ecological processes indicated that heterogeneous selection was the major process (46%-70%) governing the community assembly of fish microbiomes, whereas the undominated process (64%) was found to be more important for the water microbiome. The diversity pattern showed that β-diversity (75%) of the metacommunity overweight the α-diversity (25%), confirming that the niche separation of microbial communities in different habitats and host selection were important to shape the fish-associated microbial community structure. This study enhances our mechanistic understanding of fish-associated microbial communities in different habitats, and has important implications for analyzing host-associated metacommunities.